2011
DOI: 10.1007/s10900-011-9535-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Barbers Regarding Hepatitis B and C Viral Infection in Sana’a City, Yemen

Abstract: There is strong evidence that razors, barber's scissors, nail files and body piercing instruments are risk factors for transmission of hepatitis B and C. to investigate the knowledge, attitudes and practices regarding hepatitis B and C virus among barbers in Sana'a city. KAP study was conducted from July-September 2011. Two hundred and thirty four barbershops were surveyed. Out of 234 barber shops, 73.1% heard about viral hepatitis B and C. The awareness of modes of transmission of hepatitis and the different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 14 publications
4
12
1
2
Order By: Relevance
“…The practice of using a new blade for every customer was common, as reported, among 90% of the barbers. This finding is consistent with other studies and indicates a uniform improvement in the practices of barbers across different countries [2,17,21]. We did not perform a regression analysis due to an insufficient number of HBV cases.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The practice of using a new blade for every customer was common, as reported, among 90% of the barbers. This finding is consistent with other studies and indicates a uniform improvement in the practices of barbers across different countries [2,17,21]. We did not perform a regression analysis due to an insufficient number of HBV cases.…”
Section: Resultssupporting
confidence: 91%
“…The majority of them were willing to get tested for HBV, a finding similar to that reported in a study from Hyderabad [3]. However, a lower percentage of barbers, i.e., 45.1% were willing to get tested for HBV in a study from Yemen [21]. The proportion of barbers willing…”
Section: O R I G I N a L P A P E R In Abbasi Et Alsupporting
confidence: 80%
See 1 more Smart Citation
“…The prevalence of HBV and HCV is known to differ across countries and may also differ based on the individual characteristics and conditional factors (7,8). Hepatitis B virus and HCV infections are common causes of occupational blood-borne diseases that can be transmitted between barbers and their clients and frequently lead to a chronic asymptomatic carrier condition for a long time before the development of severe end-stage liver diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, HBV and HCV infections have been implicated as an occupational hazard of the barbers (7). Previous studies have indicated that in developed countries, certain beauty treatments play an important role in the speared of HBV and HCV infection among barbers and their clients (8). Hepatitis B virus can survive on the instrument, tabletops and workbenches for at least seven days; therefore, it is important for the barbers to know their HBV status by being screened for the HBV surface antigen and antibody and to be vaccinated against HBV if found to be unprotected (4,9).…”
Section: Introductionmentioning
confidence: 99%